METODE NAWA : INTEGRASI BELAJAR AL-QUR’AN DAN BAHASA ARAB UNTUK SISWA FASE A - Andra Maya Kusuma Paramata; Endin Mujahidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Qur'an and Arabic are closely related, but are still separate in learning. Phase A students (aged 6-8 years) need an interactive approach to make it easier to understand and apply the material. This study aims to analyze the effectiveness of the NAWA (Nadwah Al-Qur'an Wa Arabiyyah) method in integrating Qur'an and Arabic learning with the concept of edutainment based on discussion, exploration, and direct experience. This study uses a research and development (R&D) method with the Borg & Gall model. Data were collected through pretest and posttest, then analyzed using the Shapiro-Wilk normality test and paired t-test. The results showed that the data were normally distributed (p> 0.05), but there was no significant difference between the pretest and posttest (p = 0.4707). Although statistically insignificant, the NAWA method provides a more interactive and enjoyable learning experience for students. Factors such as duration of implementation, teacher readiness, and student characteristics can affect the effectiveness of learning. Therefore, further research is recommended to extend the application of the NAWA method and try it at higher levels of education to test its effectiveness in improving understanding of the Qur'an and Arabic in greater depth.